Synthesis and characterization of starch-based nanoparticles for wastewater treatment - Jeremy, Chon. (Universiti Malaysia Sarawak (UNIMAS), 2005)
Cross-l inked carboxymethyl sago starch and tapioca starch were prepared by cross-linking with POCi) and carboxymethylated with sodium chloroacetate. The ability of these starch derivatives and their effectiveness to remove various divalent metal ions in aqueous solution were investigated. The different factors affecting metal ions adsorption on the cross-linked carboxymethyl sago starch and tapioca starch such as pH, types of starches, initial metal ion concentration and treatment time were studied. Tapioca starch had shown to be a more effective adsorbent as compared to sago starch in removing heavy metal ion from aqueous solution. The removal effectiveness of metal ions by these cross-linked carboxymethyl starch are in the following order of Pb2 + > Cu2 + > Ni2 +. Adsorption capacities of cross-linked carboxymethyl starch were affected by the pH of heavy metal ions solution. Cross-linked carboxymethyl tapioca starch was found to remove 92.2% of Pb2+, 80.7% of Cu2 + and 78.0% of Ni2+ from 100 ppm metal ion solution in the condition of pH 6.0. Cross-linked carboxymethyl starch can be used as an alternative adsorbent for heavy metal ions in wastewater treatment.